(untitled) (INNOVATIVE ECONOMY, 2025)
Borysiak O.V. IMPERATIVE OF INTELLECTUALIZATION OF THE BUSINESS MANAGEMENT SYSTEM IN THE CONTEXT OF STRENGTHENING INNOVATIVE ACTIVITY AND COMPETITIVENESS OF ENTERPRISE Purpose. The purpose of the article is to identify the imperative pattern of strengthening the innovative activity and competitiveness of enterprise through the transformation of the business management system based on intellectualization. Methodology of research. System analysis was used to examine the components of the enterprise ecosystem from the perspective of the need to strengthen innovation activity and competitiveness. Methods of abstraction and dialectical cognition made it possible to highlight the imperative of intellectualizing the business management system. The use of the generalization method made it possible to identify the features of technologies for intellectualizing the business management system to enhance the innovative activity and competitiveness of enterprise. Findings. The strategy of innovative development of enterprise is linked to the implementation of changes and risk prevention, which requires identifying business processes from the perspective of their sustainability and conditions for the emergence of possible risks. It is noted that the innovative activity of enterprise involves constant interaction with the external environment and sustainable internal marketing. The intellectualization of business management systems is considered a way to establish customer-oriented positioning in the market, a component of strengthening innovative activity and the competitiveness of enterprise. Optimizing business processes based on intellectualization helps structure the stages of doing business, make transactions more transparent, and boost customer engagement and service accessibility. The features of technologies for the intellectualization of business management systems to enhance the innovative activity and competitiveness of enterprises are summarized. The importance of the role of STEM laboratories in enhancing the innovative activity and competitiveness of enterprises, as well as the influence of AI (artificial intelligence) agents are highlighted. Originality. Further development of provisions has been made in strengthening innovative activity and competitiveness of enterprises under conditions of business management system transformation based on intellectualization, a distinctive feature of which is the imperative integration of digital technologies into business processes, the development and testing of innovative products in STEM laboratories, involvement of AI (artificial intelligence) agents in business processes. Practical value. The research results will help enterprises strengthen their innovation activity and competitiveness through the use of modern digital technologies, in particular artificial intelligence and immersive technologies, to optimize business processes as a result of cooperation with representatives of science and information technologies. Key words: business digitalization, digital technologies, artificial intelligence, innovation, innovative activity of an enterprise, competitiveness, investments, business development management, sustainable development.